2003
DOI: 10.2196/jmir.5.3.e20
|View full text |Cite
|
Sign up to set email alerts
|

Designing Tailored Web-Based Instruction to Improve Practicing Physicians' Preventive Practices

Abstract: BackgroundThe World Wide Web has led to the rapid growth of medical information and continuing medical educational offerings. Ease of access and availability at any time are advantages of the World Wide Web. Existing physician-education sites have often been designed and developed without systematic application of evidence and cognitive-educational theories; little rigorous evaluation has been conducted to determine which design factors are most effective in facilitating improvements in physician performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
0
48
0
1
Order By: Relevance
“…The Internet has expanded opportunities for the provision of a flexible, convenient, and interactive form of CME/CPD for busy practitioners who have difficulty attending formal education sessions (Casebeer et al 2003;Sly et al 2006). A consortium of the Canadian medical school CME/CPD departments has developed MDcme.ca, an Internet-based CME portal which provides College of Family Physicians of Canada (CFPC) accredited online CME courses .…”
Section: Strategies To Enhance Cme/cpd Access For Rural Physiciansmentioning
confidence: 99%
“…The Internet has expanded opportunities for the provision of a flexible, convenient, and interactive form of CME/CPD for busy practitioners who have difficulty attending formal education sessions (Casebeer et al 2003;Sly et al 2006). A consortium of the Canadian medical school CME/CPD departments has developed MDcme.ca, an Internet-based CME portal which provides College of Family Physicians of Canada (CFPC) accredited online CME courses .…”
Section: Strategies To Enhance Cme/cpd Access For Rural Physiciansmentioning
confidence: 99%
“…These approaches are emphasized in adult learning theories such as constructivism, 19 derived cognitive flexibility theory, 20 andragogy, 21 and situated learning, 22 which are relevant to online CME design. 23,24 Despite a growing body of literature on Web-based health professional education, [25][26][27] few rigorous studies of Web-based CME have been reported. These have included self-controlled trials, [28][29][30] controlled trials, [31][32][33] and randomized controlled trials (RCTs).…”
mentioning
confidence: 99%
“…20,21 Tailoring educational content to readiness to adopt a performance change is also likely to play a key role. [22][23][24][25] The Transtheoretical Model (TTM) is an integrative model that describes behavior change as a progression through a series of five stages of readiness: (1) Precontemplation: not intending to adopt the best practices, (2) Contemplation: intending to adopt the best practices in the next six months, (3) Preparation: intending to adopt the best practices in the next 30 days, (4) Action: adopted the best practices less than six months ago, and (5) Maintenance: adopted the best practices more than six months ago. The TTM could provide a useful framework for tailoring CME content in that leveraging the principles of the TTM permits the inclusion of behavior change statements to ensure activities meet the needs of all physicians, even those who are not prepared to adopt the desired performance.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%